2010
DOI: 10.1002/ptr.3311
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active sesquiterpene coumarins fromFerulaspecies

Abstract: Extracts from different species of the genus Ferula (Apiaceae) have had various biomedical applications for many centuries. Many biological features of this genus such as cytotoxicity, antibacterial, antiviral, P-glycoprotein (P-gp) inhibitory and antiinflammatory activity have been attributed to sesquiterpene coumarins; structures containing a common coumarin group and a sesquiterpene moiety. This both highlights the importance of sesquiterpene coumarins as biologically active natural products and necessitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 63 publications
0
75
0
Order By: Relevance
“…Galbanic acid (GA) and its ester, methyl galbanate, are natural products belonging to the class sesquiterpene coumarins (Figure 1) (Nazari & Iranshahi, 2011). Sesquiterpene coumarins mostly occur in the genus Ferula (Apiaceae), particularly F. galbaniflua Boiss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galbanic acid (GA) and its ester, methyl galbanate, are natural products belonging to the class sesquiterpene coumarins (Figure 1) (Nazari & Iranshahi, 2011). Sesquiterpene coumarins mostly occur in the genus Ferula (Apiaceae), particularly F. galbaniflua Boiss.…”
Section: Introductionmentioning
confidence: 99%
“…& Buhse. These compounds have shown various biological activities including anti-inflammatory, antitumor, cytotoxic, and antiviral activities (Gliszczyńska & Brodelius, 2012;Iranshahy & Iranshahi, 2011;Nazari & Iranshahi, 2011). Among the sesquiterpene coumarins, GA has drawn special attention for its promising biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The major protective effect of ajwain by UAS extract is referred to phenolic compounds particularly thymol content Kavoosi and Rowshan (2013) and Nazari and Iranshahi (2011) reported that antioxidant activities may be attributed to the presence of phenols, flavonoids, sesquiterpenes and sulfur-containing compounds in the ajwain. Such antioxidant activities could diminish oxidative damage in foodstuff (Nazari and Iranshahi 2011;Kavoosi and Rowshan 2013).…”
Section: Resultsmentioning
confidence: 98%
“…These results were in line with a previous study in which the data exhibited that the absolute methanol have a greater yield than ethanol. [37] Some study also exhibited the aqueous and alcoholic extracts tested for in vitro cytotoxicity study. [38] The result showed that aqueous extracts were considered to be less cytotoxic to these cells than their alcoholic extracts of the species.…”
Section: Antidiabetic Activitymentioning
confidence: 99%